Ar-Rum Financing Analysis on the Development of Micro, Small and Medium Enterprises (MSMEs) (Case Study of PT. Pegadaian (Persero) Mandailing Natal Sharia Service Unit) - Yeni Aprilinda Lubis; Tri Inda Fadhila Rahma (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Financing is an activity in channeling funds to parties other than banks based on sharia principles. The distribution of funds in the form of financing is based on the trust given by the owner of the funds to the users of the funds in the form of financing that will surely pay off. The purpose of this study was to determine the operational mechanism of Ar-rum financing and Ar-rum’s financing impact on the development of MSMEs. Based on the research results, the customers of Ar-rum Financing are customers who have a business and have been running for at least 1 year. The operational mechanism of Ar-Num Financing is, first, the pawnshop receives the application file for Ar-run financing from the customer, secondly checks the validity of the documents attached by the customer and conducts business feasibility analysis interviews and assesses the collateral. Third, the disbursement of Ar-rum’s financing funds after signing a financing agreement known to the husband and wife. After customers receive Ar-rum financing, the average customer income increases every month.